Shielding at a distance due to anomalous resonance - Sanghyeon Yu; Mikyoung Lim (New Journal of Physics, 2017)
A cylindrical plasmonic structure with a concentric core exhibits an anomalous localized resonance which results in cloaking effects. Here we show that if the structure has an eccentric core, a new kind of shielding effect can happen. In contrast to conventional shielding devices, our proposed structure can block the effect of external electrical sources, even in a region which is not enclosed by any conducting materials. In fact, the shielded region is located at a distance from the device. We analytically investigate this phenomenon by using the Möbius transformation, through which an eccentric annulus is transformed into a concentric one. We also present several numerical examples.